2012
DOI: 10.1016/j.anifeedsci.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between ileal digestibility of amino acids and chemical composition of soybean meals in broilers at 21 days of age

Abstract: The correlations between chemical composition and coefficient of standardized ileal digestibility (CSID) of crude protein (CP) and amino acids (AA) were determined in 22 soybean meal (SBM) samples originated from USA (n = 8), Brazil (BRA; n = l) and Argentina (ARG; n = l) in 21-day oíd broilers. Birds were fed a commercial maize-SBM diet from 1 to 17 days of age followed by the experimental diets in which the SBM tested was the only source of protein (205g CP/kg) for three days. Also, in vitro nitrogen (N) dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
23
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 46 publications
9
23
4
Order By: Relevance
“…This information may help to know which level of ANF concentration could adversely affect the animals and thereby could help to intervene that reducing the negative impacts of ANF. The results agree with those of Frikha et al (2012) who reported that protein solubility, TI, and UA correlate with the amounts of unheated soybeans in the diet. During the early periods (1 -10 d and 1 -24 d), increasing the level of RSBM in the diets had no influence on the FI, but the FI was decreased when considered over the entire trial period (1 -35 d).…”
Section: Discussionsupporting
confidence: 83%
“…This information may help to know which level of ANF concentration could adversely affect the animals and thereby could help to intervene that reducing the negative impacts of ANF. The results agree with those of Frikha et al (2012) who reported that protein solubility, TI, and UA correlate with the amounts of unheated soybeans in the diet. During the early periods (1 -10 d and 1 -24 d), increasing the level of RSBM in the diets had no influence on the FI, but the FI was decreased when considered over the entire trial period (1 -35 d).…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, this method allows to assess whether these interfering factors affect the intercept or the slope of the relationship (Loncke et al, 2009). The mean concentrations that we determined for CP, fibre and EAA contents in SBM were higher than the averages published by Goerke et al (2012), but were within the ranges previously reported by Frikha et al (2012) andNRC (2012).…”
Section: Discussionsupporting
confidence: 75%
“…Processing (De Coca-Sinova et al, 2008) and chemical composition of the original beans (Dilger et al, 2004) affect the response of pigs to the inclusion of SBM in the diet. Frikha et al (2012) and Rebollar et al (2013) reported that SBM from US beans had more CP and sucrose, less NDF and higher KOH solubility and protein dispersibility index values than SBM from ARG. Consequently, country of origin of the original beans might affect the energy content and protein quality of the SBM.…”
Section: Soya Bean Meal Source In Piglet Dietsmentioning
confidence: 99%
“…Several studies (Frikha et al, 2012;Rebollar et al, 2013) have shown that protein quality and AA digestibility of the SBM varied with the country of origin of the beans. A difference in protein quality might be more important and easy to detect in young pigs rather than in adult pigs because its gastrointestinal tract is less developed.…”
Section: Introductionmentioning
confidence: 99%